Does Your Loved One With Cognitive Symptoms Need to See a Doctor? Check It Online - Agüera-Ortiz, Luis; Martín-Carrasco, Manuel; Arriola-Manchola, Enrique; Martínez-Lage, Pablo; Pérez-Martínez, David Andrés; Ojea, Tomás; Soler-López, Begoña; García-Ribas, Guillermo (Frontiers in Computational Neuroscience, 2022)
Widespread access to emerging information and communication technologies (ICT) allows its use for screening of diseases in the general population. At the initiative of the Spanish Confederation of Associations of Families of People with Alzheimer's disease and other dementias (CEAFA), a website (http://www.problemasmemoria.com) has been created that provides information about Alzheimer’s disease and include questionnaires to be completed by family or friends concerned about memory problems of a relative. A cross-sectional, randomized, multicenter study was performed to evaluate feasibility, validity, and user satisfaction with an electronic method of completion versus the current method of paper-based questionnaires for clinically dementia screening completed by the informants: the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) and the Alzheimer’s disease-8 screening test (AD8). A total of 111 pairs were recruited by seven memory clinics. Informants completed IQCODE and AD8 questionnaires both in their paper and electronic versions. The correlation between paper and electronic versions was significantly positive for IQCODE (r= 0.98; p< 0.001) and AD8 (r= 0.96; p< 0.001). The execution time did not differ significantly, and participants considered their use equally easy. This study shows that an electronic version of the IQCODE and AD8 questionnaires are suitable for its on-line use via internet and achieve the same results as the traditional paper versions.